The Role of the Nurul Hidayah Integrated Taklim Council in Meeting the Religious Learning Needs of the Elderly in Cirebon Regency - Suryadi; Kamil, Mustofa; Saepudin, Asep; Saripah, Iip; Nursahidin; Rahman, Amelia Fauziyah (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study is to explore the human resource development system through education and da'wah training of the Nurul Hidayah taklim assembly in Cirebon, Indonesia. This research uses qualitative methods. The results showed that the Nurul Hidayah assembly applied various methods such as lectures, discussions, questions and answers, practices, and field visits, all of which were designed according to the conditions and needs of the congregation. Activities in this meeting are held every week, not only focusing on routine recitation but also prioritizing the self-development of the congregation, including religious, social, and economic aspects. Regular recitation involves the process of takwin, tanzim, and taudi', which includes dhikr, public lectures, and religious lessons to form moderate and independent religious congregations. In addition, there is corpse management training that provides knowledge and skills in managing corpses in accordance with Islamic law, as well as Hajj and Umrah management training that increases pilgrims' understanding of Hajj and Umrah. The tadabbur alam program is also implemented as a learning tool to get to know God's creation more closely and cleanse the soul. The role of Islamic extension workers is very important in the implementation of all these programs, demonstrating the commitment of the taklim assembly in developing the religious and social capabilities of the congregation with a flexible and adaptive approach.